CHARACTERISTICS OF CLINICAL AND PSYCHOPATHOLOGICAL INDICES IN ALCOHOL DEPENDENCE IN PERSONS WITH CONSTANT TYPE OF ALCOHOL ABUSE IN COMPLIANCE WITH BIOLOGICAL RHYTHMS - Zhyvotovska, L.V.; Paida, Y.Y.; Borysenko, V.V.; Bodnar, L.A.; Makarenko, N.A. (World of Medicine and Biology, 2020)
Among the current issues of modern addiction medicine is the problem of studying the psychopathological manifestations of mental and behavioral disorders due to alcohol consumption, their pathogenetic mechanisms and consideration of these factors in the development of therapeutic methods. As a result of psycho-emotional study, taking into account the biorhythm status, it was noted that in persons of evening type prevailed the high level of state and trait anxiety in comparison with morning and undifferentiated type (p